Homogenizing Estimates of Heritability Among SOLAR-Eclipse, OpenMx, APACE, and FPHI Software Packages in Neuroimaging Data - Kochunov, Peter; Patel, Binish; Ganjgahi, Habib; Donohue, Brian; Ryan, Meghann; Hong, Elliot L.; Chen, Xu; Adhikari, Bhim; Jahanshad, Neda; Thompson, Paul M.; Van’t Ent, Dennis; den Braber, Anouk; et al. (Frontiers in Neuroinformatics, 2019)
Imaging genetic analyses use heritability calculations to measure the fraction of phenotypic variance attributable to additive genetic factors. We tested the agreement between heritability estimates provided by four methods that are used for heritability estimates in neuroimaging traits. The SOLAR-Eclipse and OpenMx use iterative maximum likelihood estimation (MLE) methods. The APACE and FPHI, employ fast, non-iterative approximation-based methods. We performed this evaluation in a simulated twin-sibling pedigree and phenotypes and with diffusion tensor imaging (DTI) data from three twin-sibling cohorts, the HCP, NTR and BrainSCALE projects provided as a part of the ENIGMA consortium. We observed that heritability estimate may differ depending on the underlying method and dataset. The heritability estimates from the two MLE approaches provided excellent agreement in both simulated and imaging data. The heritability estimates for two approximation approaches showed reduced heritability estimates in datasets with deviations from data normality. We propose a data homogenization approach (implemented in solar-eclipse, www.solar-eclipse-genetics.org) to improve convergence of heritability estimates across different methods. The homogenization steps include consistent regression of any nuisance covariates and enforcing normality on the trait data using inverse Gaussian transformation. Under these conditions, the heritability estimates for simulated and DTI phenotypes produced converging heritability estimates regardless of the method. Thus, using these simple suggestions may help new heritability studies to provide outcomes that are comparable regardless of software package.